PROSPECTIVE STUDY ON THE EFFECT OF PHARMACEUTICAL CARE ON MATERNAL AND FETAL OUTCOMES IN GESTATIONAL AND PREGESTATIONAL DIABETIC PATIENTS - ELBERRY, AHMED ABDULLAH; RABEA, HODA; MOHSEN, SHIREEN M.; MOURAD, ABDEL-REHIM; KINAWY, GAAFAR (International Journal of Pharmacy and Pharmaceutical Sciences, 2022)
Objective: The prevalence of diabetes in pregnancy has increased in the U. S. The majority is gestational diabetes mellitus (GDM), with the remainder primarily preexisting type 1 diabetes and type 2 diabetes (pregestational diabetes, PGDM). The present study investigates the demographics and clinical differences between both types. Methods: This prospective study was conducted on ninety pregnant females with normal menstrual cycles before pregnancy. Demographics, oral glucose tolerance test (OGTT), and HbA1c were assessed. Results: There was a significant difference in the term of Oral glucose tolerance test Week 24 during fasting, Oral glucose tolerance test Week 24 after one hour, Oral glucose tolerance test Week 24 after two hours, Oral glucose tolerance test Week 24 after three hours, Oral glucose tolerance test Week 28 during fasting, Oral glucose tolerance test Week 28 after one hour, Oral glucose tolerance test Week 28 after two hours, Oral glucose tolerance test Week 28 after three hours, HbA1c week 24 and HbA1c week 28; p-value<0.05. Conclusion: pregnant women in this study who needed insulin were educated to self-monitoring of blood glucose, diet control, medication adherence, and exercise, and we adjusted the needed insulin dose for them with restrictive follow-up.